การเกิดปัญญาของผู้ให้การปรึกษาเชิงจิตวิทยาแนวพุทธที่มีประสบการณ์ในการทำงานสูง - วรากร ศรสุรินทร์ (จุฬาลงกรณ์มหาวิทยาลัย, 2021)
This is a qualitative study applying an interpretative phenomenological analysis to investigate experienced Buddhist counselling service providers’ experience of emerging Panna in professional context. Key informants are six experienced Buddhist counselling service providers. Data was collected by in-dept semi-structured interview. Research results consist of four main themes  (1) being disturbed during counselling session and living due to suffering including being irritable and disturbed during counselling session (having unclear mind and disturbed thought and misperceiving clients’ stories) and being disturbed in life due to suffering (ruminating about the mistake in the counseling session, being discontented doubtful and disappoint in oneself and triggering other sufferings)  (2) being aware making sense and striving to alleviate suffering including being aware and attended to suffering (being in touch with suffering state and being motivated to explore and alleviate suffering) being settled and re-examine the situation when appropriated (attend to calmness and appropriateness and explore and re-examine the suffering situation) being aware of expectation overlapping with the suffering (comprehending that the source of suffering come form within and contradict with reality and working with the source of suffering) and clearing the remaining suffering which come back  (3) cultivating important factors for emerging Panna and alleviate suffering (being apprehensive alleviating suffering due to emerging Panna and  cultivating mindfulness concentration and insight to comprehend reality) and  seeing through reality and living in harmony with the present moment (living with the present moment with light and peaceful mind and crystallizing lessons from the workthroughed suffering)  (4) valuing and cultivating mindfulness and Panna consistently including being mindful and having Panna as a foundation of professional and personal life (perceiving Panna as important in professional life and perceiving Panna as important in life) and practicing mindfulness and Panna in daily life